Values Education In Alternative Education Approaches - Candemir, Burcu; Tunç, Yunus; Açar, Davut; Sağlam, Mehmet (Fırat University, 2022)
Early childhood is a period in which critical developments are completed for children. During this period, the child develops in the areas of physical, cognitive, lingual, social-emotional and self-care skills. In this period, as the child interacts with the social environment, he encounters the social reflection of the concept of value. Value appears as a concept that is imposed on people. Respect, love, helpfulness, sharing are just a few of these values. The child comes into contact with and adopts these values in society, starting with his family, which is his first social environment. In the early childhood period, preschool education environments offer a rich stimulating environment to the child. Values are added to the education program as "values education" in pre-school education environments and are processed in a blended manner within the program. However, values education is handled from different perspectives not only in preschool education program but also in alternative education approaches. These alternative education approaches can be listed as Montessori, Reggio Emilia, Waldorf education approaches, Open Education, Bank Street (Developmental Interaction), Child to Child, Head Start, High Scope and Project approaches. This research aims to provide information on values education practices in alternative education approaches in the literature.

Erken çocukluk dönemi çocuklar için kritik gelişmelerin tamamlandığı bir dönemdir. Bu dönemde çocuk fiziksel, bilişsel, dil, sosyal-duygusal ve öz bakım becerileri alanlarında gelişmektedir. Bu dönemde çocuk sosyal çevre ile etkileşim kurdukça değer kavramının toplumsal yansımasıyla karşılaşmaktadır. Değer, insana yüklenen bir kavram olarak karşımıza çıkmaktadır. Saygı, sevgi, yardımseverlik, paylaşma, bu değerlerden yalnızca birkaç tanesidir. Çocuk, ilk sosyal çevresi olan ailesinden başlamak üzere toplumda bu değerlerle temas etmekte ve benimsemektedir. Erken çocukluk döneminde okul öncesi eğitim ortamları çocuğa zengin uyarıcı bir çevre sunmaktadır. Değerler okul öncesi eğitim ortamlarında eğitim programına “değerler eğitimi” olarak eklenmekte ve programın içerisinde harmanlanmış şekilde işlenmektedir. Ancak değerler eğitimi yalnızca okul öncesi eğitim programında değil alternatif eğitim yaklaşımlarında da farklı bakış açılarıyla ele alınmaktadır. Bu alternatif eğitim yaklaşımları; Montessori, Reggio Emilia, Waldorf eğitim yaklaşımları başta olmak üzere Açık Eğitim, Bank Street (Gelişimsel Etkileşim), Çocuktan Çocuğa, Head Start, High Scope ve Proje yaklaşımı olarak sıralanabilir. Bu araştırma, literatürde alternatif eğitim yaklaşımlarında değerler eğitimi uygulamalarına yönelik bilgi vermeyi amaçlamaktadır.
ALTERNATİF EĞİTİM YAKLAŞIMLARINDA DEĞERLER EĞİTİMİ